SPECIALIZATION IN HIGHER EDUCATIONAL INSTITUTIONS TEACHING SUBJECTS - Dilshod Polotovich Mirzoev (Scholar Express Journal, 2021)
This article presents a clear formulation of teaching techniques is a key factor in improving the quality of the lesson. The fact that the mass education together with the technology will be conducted on the basis of a clear plan of practical training will serve to improve the quality of Education. Specialty subjects are shown with examples of obtaining an effective result using advanced pedagogical technologies
Keywords: Personnel; Independent; Method; Qualification; Skill; Leader